Validação do single leg bridge test, pico de torque isométrico de flexão do joelho e Pivot-Agility Test como critérios para retorno ao esporte após reconstrução do ligamento cruzado anterior - Rodrigues, Carlos Augusto Silva (2023)
Introduction: Muscular strengths and symmetries of knee extension and flexion are among the most indicated characteristics for evaluation in patients after anterior cruciate ligament (ACLR) reconstruction surgery with the aim of returning to sports. However, the financial cost of acquiring equipment such as an isokinetic dynamometer is a barrier to implementing the gold standard in practice. Clinicians have used functional tests and manual isometric dynamometry as alternatives, however there is a scarcity of scientific evidence that proves the discriminative validity of these tests for the assessment of knee flexion symmetry strength. In addition, the current criteria established for returning to sports are insufficient to predict a safe return to sports and other tests that evaluate other constructs such as agility have been presented as a possibility of reinforcement, increasing the probability of returning to sports practice. Objective: To analyze the clinimetric properties and discriminative validity of the Pivot-Agility test (PAT) for measuring the agility construct and single leg bridged test (SLBT) and manual isometric knee flexion dynamometry for measuring muscle strength and symmetry in patients after ACLR Methods: We included participants who were at least 6 months after ACLR surgery. On the first day of assessment, participants answered questionnaires about self-reported function and psychological readiness and performed SLBT, isometric knee flexion dynamometry, isokinetic knee extension and flexion dynamometry in sequence, and repeated the SLBT and isometric knee flexion dynamometry to enable measurements of test-retest reproducibility. On the second day, they performed the PAT, T agility test, hop tests in sequence, and repeated the PAT to enable test-retest measurements. Results: 132 participants were eligible, with 127 performing the SLBT test and retest, 124 performing isometric knee flexion strength and 103 PAT. The predominantly male sample (91.3%), with a mean age of (27.6 ±7.6) years, postoperative time of (14.9±15.9) months and predominant graft of the flexor muscle of the knee (92.9%). The intraclass correlation coefficient (ICC) of the PAT was (ICC: 0.95; 95%CI: 0.96-0.98), SLBT (ICC:0.87; 95%CI: 0.82-0, 90) in the injured limb and (ICC: 0.85; CI95%: 0.79 – 0.89) in the uninjured limb, while isometric dynamometry of the injured limb (ICC: 0.89; CI95%: 0.85- 0.92) and (ICC: 0.85; CI95%: 0.78-0.89) in the uninjured limb. PAT showed excellent validity when compared to the T agility test (r = 0.90; p< 0.01) and discriminative validity with a cutoff point of 11.53sec analyzed by ROC curve. SLBT and manual isometric dynamometry showed a low degree of correlation with isokinetic measures for muscle strength and symmetries and cutoff points with low values of sensitivity and specificity. Conclusion: PAT presents adequate validity, concordance and reproducibility, in addition to association with other tests that help in the decision-making process to return to sport. SLBT and isometric dynamometry show good agreement and reproducibility, but questionable validity. The results of the present study confirm the possibility of using these tools, noting the limitations of inferring results in patients after ACLR who are returning to sports.